Factors associated with the intake of traditional foods in the Eeyou Istchee (Cree) of northern Quebec include age, speaking the Cree language and food sovereignty indicators. Issue 1 (1st January 2018) - Noreen, Willows; Johnson-Down, Louise; Jean-Claude, Moubarac; Lucas, Michel; Robinson, Elizabeth; Batal, Malek
ABSTRACT: The Eeyouch are a First Nations (Cree) population that live above 49.6°N latitude in Eeyou Istchee in northern Quebec. Eeyouch rely on traditional foods (TF) hunted, fished or gathered from the land. The overarching aim of this study was to achieve an understanding of the factors associated with TF intake among Eeyouch . Data were from 465 women and 330 men who participated in the Nituuchischaayihtitaau Aschii Multi-Community Environment-and-Health (E&H) study. The relationship between TF consumption and dietary, health, sociodemographic and food sovereignty (i.e. being a hunter or receiving Income Security to hunt, trap or fish) variables was examined using linear and logistic regression. Analyses were stratified by sex because of the male/female discrepancy in being a hunter. Among respondents, almost all (99.7%) consumed TF, 51% were hunters and 10% received Income Security. Higher intake of TF was associated with lower consumption of less nutritious ultra-processed products (UPP). In women, TF intake increased with age, hunting and receiving Income Security, but decreased with high school education. In men, TF intake increased with age and speaking only Cree at home. The findings suggest that increased food sovereignty would result in improved diet quality among Eeyouch through increased TF intake and decreased UPP intake.